TEORI-TEORI PESERTA DIDIK DALAM PENDIDIKAN DI SMA ISLAM AL-ULUM TERPADU - Diva Nur Annisa Wijaya; Milawani Milawani; M. Ikhsan Kurniawan; Afrahul Fadhila Daulay (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
Educational theory is the foundation and starting point for the development of educational practices, for example curriculum development, school management and the teaching and learning process. Theory in education is an example of the development of an active learning education model where the learning process is not just about the teacher or students but teachers and students have a very important role in determining optimal learning outcomes. The aim of this research is to find out how teachers apply effective student learning theories at Al-ulum Integrated Islamic High School so that learning outcomes are achieved.